Interfacial electronic structure of Cl6SubPc non-fullerene acceptors in organic photovoltaics using soft X-ray spectroscopies. Issue 47 (22nd November 2017) - Lee, Hyunbok; Ahn, Sun Woo; Ryu, Sim Hee; Ryu, Bo Kyung; Lee, Myeung Hee; Cho, Sang Wan; Smith, Kevin E.; Jones, Tim S.
Abstract : The significantly high energy gap between a SubPc donor and a Cl6 SubPc acceptor is the origin of high V OC in OPVs. Abstract : In organic photovoltaics (OPVs), determining the energy-level alignment of a donor and an acceptor is particularly important since the interfacial energy gap between the highest occupied molecular orbital (HOMO) level of a donor and the lowest unoccupied molecular orbital (LUMO) level of an acceptor ( E DHOMO– E ALUMO) gives the theoretical maximum value of the open-circuit voltage ( V OC ). To increase the E DHOMO– E ALUMO, non-fullerene acceptors, which have a lower electron affinity (EA) than C60, are receiving increasing attention. In this study, we investigated the energy-level alignment at the interface of a boron chloride subphthalocyanine (SubPc) donor and a halogenated SubPc (Cl6 SubPc) acceptor using soft X-ray spectroscopy techniques. The estimated E DHOMO– E ALUMO of Cl6 SubPc/SubPc was 1.95 eV, which was significantly higher than that of 1.51 eV found at the interface of C60 /SubPc. This increased E DHOMO– E ALUMO was the origin of the enhanced V OC in OPVs. Additionally, we studied the molecular orientation of Cl6 SubPc using angle-dependent X-ray absorption spectroscopy. The highly disordered Cl6 SubPc molecules result in low carrier mobility, which contributes to the lower short-circuit current density of the Cl6 SubPc acceptor OPVs than the C60 acceptor OPVs.